PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DAGING SAPI BEKU DAN SEGAR (Studi Pada Pelanggan PT. Anzindo Gratia International) - Tatag Herbayu (Jurnal Ekonomi dan Industri, 2019)
This study aims to obtain factual and conceptual information about the effect of Product Quality and Service Quality on Customers of PT. Anzindo Gratia International. Questions is structured using a Likert Scale. Samples taken were 40 respondents. The sampling test technique uses the census method and data collection techniques including validity test, reliability test, classic assumption test and multiple linear regression test and hypothesis test. The results of the study, variable product quality and service quality have an influence on simultaneously, the two predictor variables have a fluctuating linear effect on customer satisfaction with a good level of significance. From the hypothesis test known that F count > F table, this shows that the variables Product Quality and Service Quality together have a significant effect on customer satisfaction. Likewise, the variables of product quality and service quality partially contribute significantly to customer satisfaction. From the partial hypothesis testing of each variable namely product quality and service quality it is known that t count > t table, from this shows that the variables Product Quality and Service Quality partially have a significant effect on changes in the value on customer satisfaction at PT. Anzindo Gratia International.